Generation of a Socio-Economic Suitability Map for Nile Tilapia (Oreochromis niloticus) Culture using Free Geographical Information System (GIS) software and Spatial Multi-Criteria Evaluation (SMCE) in Kisumu County, Kenya - Mokoro , Anne K.; Njiru , James; Matolla , Geraldine (African Journal of Education,Science and Technology (AJEST), 2022)
In recent years, aquaculture has accounted for roughly half of all fish consumed globally. Scholar’s view aquaculture to have the potential to expand sustainably if suitable fish pond sites are located guided by socio-economic criteria. The need to generate socio-economic suitability map to guide location of fish ponds is therefore critical. This study generated a socio-economic suitability map for Nile Tilapia (Oreochromis niloticus) culture using Free GIS and SMCE Software in Kisumu County, Kenya. The criteria including; distance to water source, distance to fish feed source, distance to fingerlings source availability of animal waste, potentiality of farm gate sales, distance to market, and distance to all season roads were established, standardized, weighted and each criterion categorized into a five-level suitability scale of extremely suitable, suitable, averagely suitable, slightly suitable, and not suitable. The weighted criteria were combined using SMCE module in ILWIS. The generated site suitability map in terms of socio-economic factors indicates that 68.9 % of Kisumu county is extremely suitable, 25.5 % is suitable and 5.25% is averagely suitable for O. niloticus culture. It is concluded that based on socio economic suitability criteria, the County is highly suitable for O. niloticus culture.